2018
DOI: 10.1002/ctpp.201700052
|View full text |Cite
|
Sign up to set email alerts
|

Time‐reversal invariance of quantum kinetic equations II: Density operator formalism

Abstract: Time-reversal symmetry is a fundamental property of many quantum mechanical systems. The relation between statistical physics and time reversal is subtle, and not all statistical theories conserve this particular symmetry-most notably, hydrodynamic equations and kinetic equations such as the Boltzmann equation. Here, we consider quantum kinetic generalizations of the Boltzmann equation using the method of reduced density operators, leading to the quantum generalization of the Bogolyubov-Born-Green-Kirkwood-Yvo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Section 3.3 and selected data with more advanced selfenergies that were introduced in Section 3.2. Prior to the NEGF simulations we have performed detailed numerical convergence tests that include particle number and energy conservation and time reversibility . In addition, for small systems we have performed tests against exact diagonalization calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Section 3.3 and selected data with more advanced selfenergies that were introduced in Section 3.2. Prior to the NEGF simulations we have performed detailed numerical convergence tests that include particle number and energy conservation and time reversibility . In addition, for small systems we have performed tests against exact diagonalization calculations.…”
Section: Resultsmentioning
confidence: 99%
“…However, the wavenumber range for which this is the case cannot be easily estimated beforehand; see the results in section 3.2 and Figure 4. In the presented range, it is found that one could use expansion IV (Equation (18), no q 4 terms) for an estimate of the plasmon location for higher temperatures. Near the one-particle continuum (at low T), "I" [Equation (18)] is to be preferred.…”
Section: Ab Initio Plasmon Dispersion Of the Correlated Electron Gasmentioning
confidence: 91%
“…Figure 6 summarizes the results for the plasmon dispersion and damping over a broad range of densities and temperatures corresponding to 2 ≤ r s ≤ 10 and 0.5 ≤ ≤ 2. We include the results from the weak damping approximation and from the analytical continuation of both RPA and SLFC and also the analytical approximations (18) and (16) for the RPA dispersion. The main observations on the complex behaviour are as follows.…”
Section: Ab Initio Plasmon Dispersion Of the Correlated Electron Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, our NEGF simulations have been carefully tested for convergence with respect to the time step where, among others, particle number and total energy conservation are monitored, for example, Ref. , and also time reversibility is verified. For small systems tests against exact diagonalization calculation are performed.…”
Section: Nonequilibrium Green Functions Approachmentioning
confidence: 99%